Gamified interventions to educate healthcare professionals on the rational use of antimicrobials - Sumana, Mahadevaiah Neelambike; Shettar, Supreeta R.; Maheshwarappa, Yogeesh D.; Megha, G. K.; G. S., Veerabhadraswamy; Eshwarappa, Chinchana Shylaja; S. C., Shruthi Shree (Frontiers in Microbiology, 2025)
BackgroundAntimicrobial resistance [AMR] is a global health problem. It is important to train health care professionals on the rational use of antimicrobials to curb AMR.MethodsThis prospective interventional study was conducted with clinical practitioners, undergraduates [MBBS/Interns], postgraduates and pharmacy Students. A total of 50 participants were included in the study. The innovative games were administered for the management of infections of all the different systems of the body under the Indian Council Medical Research (ICMR) treatment guidelines of 2022 and the latest Infectious Disease Society of America (IDSA) guidelines involving different components. Pre-test and post-test questionnaires were administered and evaluated.ResultsAfter the intervention, the knowledge on the ability to differentiate between bacterial and viral symptoms in respiratory tract infections and gastroenteritis improved from 48 to 94%. The practice of using the right empirical choice of antimicrobials at the right dose for the right duration, on the basis of the severity of the infection, improved from 34 to 82%. The awareness/practice of using the right and rational combination of antibiotics improved from 44 to 84%. Knowledge of suspected multidrug-resistant gram-negative infections and other priority pathogens, such as methicillin-resistant Staphylococcus aureus [MRSA] and Candida infection, has improved from 32 to 78%. The practice of using certain antibiotics at specific infection sites based on the basis of their pharmacodynamics and pharmacokinetics improved from 20 to 76%. The knowledge of the intrinsic resistance of certain microorganisms to specific antimicrobial agents has improved from 15 to 80%.ConclusionThe gamified intervention successfully improved participants’ knowledge and awareness of rational antimicrobial use. The substantial improvements in all the aforementioned components highlight the positive impact of the intervention in promoting optimal antimicrobial use and curbing AMR. Innovative gamified interventions create better and long-lasting awareness, ensuring the appropriate use of antimicrobials.